Optimisation of Chitosan as A Natural Flocculant for Microplastic Remediation - Petrus Apri Putranto; Adian Khoironi; Rifqi Ahmad Baihaqi (Journal of Emerging Science and Engineering, 2023)
The objective of this study is to determine the optimal concentration of chitosan for microplastic remediation using the coagulation-flocculation method. The chitosan concentrations employed in this study include 10, 20, 30, and 40 ppm. The process of coagulation was conducted for one minute, with a rotational speed of 120 rpm. The process of flocculation was performed for 30 minutes with a rotational speed of 60 rpm. The findings of the study indicate that chitosan demonstrates a high efficacy in microplastic removal, resulting in a removal rate of 68.3%. Furthermore, the research findings indicate that the optimal concentration of chitosan for microplastic remediation was determined to be 30 ppm. The concentration of chitosan has a direct impact on the pH, TDS, COD, and BOD values. In general, an increase in chitosan concentration leads to a drop in pH and TDS values; conversely, an increase in chitosan concentration results in a rise in COD and BOD values.